Metode Material Requirement Planning (MRP) untuk Perencanaan Kebutuhan Bahan Baku pada Produksi Songkok Nasional di UD. Iqbal VIP - Rufaidah, Anik; Lestari, Kurnia Cahya; Wahyudin, Muhammad Arif (Universitas Teuku Umar, 2021)
The right production design at a company will get effectiveness and more production efficiency, including the plan for material requirements or raw materials used by the company. In essence, planning to meet the needs of the material in a company is expected to produce an appropriate system to be applied, therefore making the production process smooth. Where this research aims to compile Material Requirement Planning (MRP) with lot-sizing technique, then compare the results to obtain the optimal combination of raw material procurement. The use of time series method on-demand uses past data, namely the last two years and the forecasting results use the additive decomposition method because this method gets a minimum error value. By using POM, the demand prediction for one year is 6951 scores. Meanwhile, the MPS results on the raw material for one year of songkok required 488 pcs of velvet cloth, 1391 kg of pelisir and 6951 scores of bos-bosan.Â From the MRP results, the PPB technique is the most optimal for planning the raw material needs of velvet, lining and boredom by ordering the purchase of natural velvet fabric as much as six times, pelisir 1 time and bos-bosan as 6 times.